Correction: cGMP dynamics that underlies thermosensation in temperature-sensing neuron regulates thermotaxis behavior in C. elegans. - PLOS ONE Staff (PLoS ONE, 2024)
[This corrects the article DOI: 10.1371/journal.pone.0278343.].